Keberlanjutan dan Green Economy dalam Industri Halal : Studi Kasus Pada Mustika Ratu Pusaka Indonesia - Hanifah, Ismahtul; Hendri Hermawan Adinugraha (Sahmiyya: Jurnal Ekonomi dan Bisnis, 2025)
The halal industry has experienced rapid development in various sectors, including food, cosmetics, pharmaceuticals and fashion. As global awareness of sustainability and green economy issues increases, the halal industry is required to adapt to environmentally friendly principles. This article discusses the integration of the concepts of sustainability and green economy in the halal industry by highlighting three main aspects: environmentally friendly halal products, the concept of zero waste, and the influence of sustainability on the competitiveness of halal products. The research method used is a literature study, by reviewing various literatures, scientific journals, and related industry reports. The results showed that environmentally friendly halal products are a new trend that global consumers are interested in. Companies are starting to replace synthetic materials with natural materials and implement sustainable agriculture. The concept of zero waste is also applied in the halal industry by recycling waste and optimizing resources to reduce environmental impact. In addition, sustainability plays a role in increasing the competitiveness of halal products, especially in international markets that increasingly demand strict environmental standards. By implementing sustainability, the halal industry is not only more competitive but also contributes to social welfare and environmental protection. Therefore, collaboration between government, industry and academia is needed to develop regulations and technologies that support a sustainable halal industry.